Lithopedion: the calcified marvel - Huchappa, Anand S.; Raghuveer, Karthik; Suresh , Anugrah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The term lithopedion was derived from the Greek words Lithos and Pedion. It is a rare ectopic pregnancy with incidence as low as 1.5-2.0% of all ectopics. An 80-year old female patient presented to the orthopaedic out-patient department with complaints of lower back pain and mild lower abdominal pain, no history of any trauma. The patient was a known case of Ttype II diabetes and hypertension on medication, no other comorbidities. The patient was referred to the department of radio-diagnosis, for plain radiograph of the lumbo-sacral spine, antero-posterior and lateral view for further evaluation. The plain radiograph revealed a well-defined oval shaped radio-density in the pelvis more towards the right side. Further evaluation was done in the form of ultrasound abdomen and computed tomography. Computed tomography revealed a mummified fetus which is in close proximity to the internal organs and adhering to bowel loop. Low socioeconomic status combined with lack of education of the population are the primary causes for delay in diagnosis resulting in undiagnosed ectopic pregnancy and its later transformation into a Lithopedion.